Ethics, professions and development concerns - Sreekumar, N. (2004)
The more the professional world locks itself within its own territorial sphere by keeping away the more important realm of general human life and its concerns, the more it ends up with various sorts of knowledge abuses. Professionals become conspirers against social interests and end up making life worst. - Reproduced.
Keywords: Ethics; Higher education; Professional personnel